TADARUS AL-QUR’AN BULAN RAMADAN: Studi Living Quran di Musala Al-Huda Desa Janti Jogoroto Jombang - Fikri Fanani; Luthfi Raziq (Jurnal Studi Qur'an dan Tafsir, 2023)
Abstract For Muslims, the Qur'an serves not only as a guide to life but also as a holy book that is read. Reading the Qur'an with tartil is highly recommended by the Prophet to his followers and is rewarded. Currently, the recitation of the Qur'an is expressed in various ways. These include reciting Surah Yusuf and Maryam to pregnant women, reciting Surah Yaasin in social gatherings, reciting the entire Qur'an, and reciting it at different times and locations. For example, the habit of practising Qur'anic 'Tadarus' in schools every morning, reciting it in people's homes every Thursday, in orphanages every day, and in Musala or Mosque every Ramadan. This research aims to explore the phenomenon of Qur'anic Tadarus every Ramadan in Musala Al-Huda Janti. This research aims to uncover the underlying noumena of this phenomenon and examine the variations in Qur'anic recitation across different locations, including differences in characteristics, management procedures, and implementation. Keywords: Tadarus Al-Qur'an, Ramadan, Musala al-Huda